The Labour of Austerity: Absurdity, Performative Resistance, and Cultural Transformation - Almeida, Nora (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2020)
This essay explores the social-psychic toll of prolonged austerity on academic librarians and the range of strategies that have (or could) serve as tools of resistance. Using a combination of theoretical analysis and autoethnography, I examine the emotional impact of bottomless and invisible labour imposed by austerity and the ways institutions use emotional coercion to promote self-surveillance, meta-work, and hyper-productivity. Following this analysis, I discuss the ways that oppressive institutional cultures silence dissent and absorb common resistance tactics advocated by educators. Finally, I introduce several examples of performance-based resistance projects and explore how creative, personal, and absurd forms of protest might be used to critique and transform the culture of work and our affective experience as knowledge workers in the neoliberal academy.